An Analysis of Reading Questions in an English Textbook for Junior High School Merdeka Curriculum Edition Based on Revised Bloom’s Taxonomy - nova, nurfadillah; Kiagus Baluqiah; Ivan Achmad Nurcholis; Eki Saputra; Washlurachim Safitri (Teaching English and Language Learning English Journal, 2025)
Abstract The Revised Bloom's Taxonomy provides a framework for evaluating cognitive levels in learning materials, and achieving a balanced distribution of lower- and higher-order thinking skills in textbooks is essential to fulfilling the objectives of the Merdeka Curriculum. This study aims to analyze the cognitive levels of reading comprehension questions in Interactive English 2 for Junior High School, Merdeka Curriculum edition, based on the Revised Bloom's Taxonomy. Using a qualitative descriptive design with document analysis, 114 reading comprehension questions across 10 chapters were examined and classified into six cognitive domains: Remembering (CI), Understanding (C2), Applying (C3), Analyzing (C4), Evaluating (C5), and Creating (C6). The analysis revealed that lower-order thinking skills dominated, with Remembering (62.28%) and Understanding (18.42%) comprising the majority, while higher-order thinking skills such as Analyzing (7.02%), Evaluating (6.14%), and Creating (3.51%) were underrepresented. These findings indicate that the textbook emphasizes factual recall and basic comprehension over critical, analytical, and creative thinking. which is inconsistent with the goals of the Merdeka Curriculum. Therefore, it is recommended that future textbook development ensure a more balanced distribution of cognitive levels to better support students' higher-order thinking skills. Keywords: English Textbook, Reading Questions, Revised Bloom's Taxonomy. Merdeka Curriculum.